2013
DOI: 10.2196/jmir.2690
|View full text |Cite
|
Sign up to set email alerts
|

Chinese My Trauma Recovery, A Web-Based Intervention for Traumatized Persons in Two Parallel Samples: Randomized Controlled Trial

Abstract: BackgroundGuided self-help interventions for PTSD (post-traumatic stress disorder) are a promising tool for the dissemination of contemporary psychological treatment.ObjectiveThis study investigated the efficacy of the Chinese version of the My Trauma Recovery (CMTR) website.MethodsIn an urban context, 90 survivors of different trauma types were recruited via Internet advertisements and allocated to a randomized controlled trial (RCT) with a waiting list control condition. In addition, in a rural context, 93 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 32 publications
6
108
1
2
Order By: Relevance
“…The observed small effects on anxiety and stress symptoms are in line with published meta-analyses of pure self-help interventions for anxiety and depression (Cuijpers et al, 2011;Spek et al, 2007). There was a medium effect size for the reduction in symptoms of post-traumatic stress; this was more similar to the reported effects of web-based self-help interventions for traumatized participants (Hirai & Clum, 2005;Wang et al, 2013) than to the effects found in the bibliotherapeutic study by Ehlers et al (2003). Bibliotherapy may be better suited to treat AjD problems than PTSD and supports our hypothesis that AjD, under its new definition as a stress response disorder, may be a particularly suitable target for self-guided, low-threshold interventions.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The observed small effects on anxiety and stress symptoms are in line with published meta-analyses of pure self-help interventions for anxiety and depression (Cuijpers et al, 2011;Spek et al, 2007). There was a medium effect size for the reduction in symptoms of post-traumatic stress; this was more similar to the reported effects of web-based self-help interventions for traumatized participants (Hirai & Clum, 2005;Wang et al, 2013) than to the effects found in the bibliotherapeutic study by Ehlers et al (2003). Bibliotherapy may be better suited to treat AjD problems than PTSD and supports our hypothesis that AjD, under its new definition as a stress response disorder, may be a particularly suitable target for self-guided, low-threshold interventions.…”
Section: Discussionsupporting
confidence: 83%
“…Despite this evidence of the clinical potential of such interventions, few studies investigated the effectiveness of self-help interventions to treat stress-related disorders such as post-traumatic stress disorder (PTSD) and AjD. Internet-based self-help interventions were effective in reducing symptoms of post-traumatic stress (Hirai & Clum, 2005;Wang, Wang, & Maercker, 2013), but a self-help booklet did not achieve a reduction of PTSD, although participants subjectively rated it to be a helpful intervention (Ehlers et al, 2003). It is possible that the inclusion of interactive elements in electronic self-help interventions, such as automated feedback or movie sequences, are responsible for the higher effectiveness of e-interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Z. Wang, Wang, and Maercker (2013) developed the Chinese My Trauma Recovery approach, a web-based intervention strategy to provide mental health help for traumatized persons. Short-term cognitive-behavioral therapy (CBT) group intervention represents a robust intervention for natural disaster victims (Y.…”
Section: Treatment Of Ptsd In Wenchuan Earthquake Survivors Psychothementioning
confidence: 99%
“…For example, for RCTs of Internet-delivered CBT in rural Scotland and China, computers had to be provided or computer centres created to allow patients to complete the program. 43,64 In addition, patients who are not technologically savvy may resist replacing clinical visits with computerized treatments.…”
Section: Box 5: Example Of Government Rollout -Australiamentioning
confidence: 99%